Song and story in biblical narrative : the history of a literary convention in ancient Israel - Weitzman, Steven, 1965- (Indiana University Press, 1997)
Journeying from ancient Egyptian battle accounts to Aramaic wisdom text to early retellings of biblical tales in the Dead Sea Scrolls, Jewish-Hellenistic literature, and rabbinic midrash, Steven Weitzman follows the history of the use of song in biblical narrative from its origins as a congeries of different literary behaviors to its emergence as a self-conscious literary convention. Weitzman shows that the perception among early Jews that biblical narrative was a normative text governing both religious and literary behavior played a catalytic role in transforming this practice into a distinctively "biblical" literary form. This book sheds light not only on one of the Bible's more perplexing literary traits but on literary practice in ancient Israel and shows how the changing literary expectations and religious sensibilities of readers can lead them to reimagine the texts they seek to understand
Keywords: Bible. -- Old Testament -- Language, style.; Bible. -- Old Testament -- Criticism, interpretation, etc.; Bible. -- A.T. -- Langue.; Bible. -- Ancien Testament -- Critique, interprétation, etc.; Bible. -- A.T. -- Style.; Bible. -- Old Testament; Bibel -- Altes Testament; Bibel; Hebrew poetry, Biblical -- History and criticism.; Narration in the Bible.; Poésie hébraïque biblique -- Histoire et critique.; Narration dans la Bible.; RELIGION -- Biblical Criticism & Interpretation -- Old Testament.; Language and languages -- Style; Hebrew poetry, Biblical; Narration in the Bible; Erzählen; Literaturgattung; Lyrik; Lied; Liederen.; Oude Testament.; Hebräisch.; Criticism, interpretation, etc.